Kajian ayat-ayat tarbawi dalam al-qur’an sebagai sumber teoritis dan praktis pengembangan ilmu pendidikan islam: Konsep dasar, prinsip-prinsip, penerapan ilmu pendidikan islam dalam kehidupan sehari-hari, kesimpulan dan implikasi pendidikan islam berdasarkan ayat-ayat tarbawi - nisak, khoirun nisak (Maliki Interdisciplinary Journal, 2025)
This paper thoroughly examines the fundamental concepts and practical applications of Islamic education derived from the Qur’an, Hadith, and human intellect as a reflective tool granted by Allah SWT. Islamic education is not merely a process of knowledge transfer but also a process of character formation and moral development, which are considered the essence of education in the Islamic worldview. This study highlights the core principles of Islamic education, including objectives, curriculum, methods, the role of educators, students, teacher-student interaction, the learning environment, and evaluation systems based on Islamic values. Moreover, this paper emphasizes the practical implementation of Islamic education in everyday life, particularly within the family and society. In the family context, values such as compassion, patience, obedience, and consultation (shura) serve as the foundation for building harmonious relationships. In the broader social context, the application of values like tolerance, mutual cooperation, justice, and brotherhood is crucial for fostering a peaceful and civilized society. Using the tafsir tarbawi approach, this paper provides both theoretical and practical contributions to the development of an Islamic education system that is relevant to contemporary challenges and the holistic needs of humanity.